PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KECERDASAN EMOSIONAL DAN JOB STRESS TERHADAP KINERJA GURU (Studi Pada Guru SMK Negeri Sub Rayon 01 Kota Semarang ) - 11.52.02.0139, Ice Faulia (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to examine and analyze the effect of Emotional Intelligence and Job Stress on Organizational Teachers Performance. Culture as Moderator Variables in Sub Rayon 01 of Semarang. The samples in this study were 136 teachers and civil servants are certified as educators in Sub Rayon 01 of Semarang . Methods of data collection using questionnaires with linkert scale in the range 1-7 , and the data used are primary data or data obtained from respondents answers to the questionnaire. A statistical technique used is multiple linear regression analysis. The results showed that the moderating influence Organization Cultural Role Emotional Intelligence and Job Stress on the Performance of teachers together can explain the variation in the performance of teachers in Sub Rayon 01 Semarang 61.7 % , the rest is explained by other factors not examined in this study . Emotional intelligence factors had a more dominant effect of 59.4 % compared to Job Stress in an effort to improve teacher performance while variable does not moderate the influence of Organizational Culture and Job Stress Emotional Intelligence to improve teacher performance in Sub Rayon 01 SMK Semarang City . Keywords : Emotional Intelligence Job Stress , Organizational Culture , and Teacher Performance.